2008
DOI: 10.1108/03056120810896218
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescent light sources via soft lithography

Abstract: Purpose: Microcontact printing is a process used to print high resolution protein arrays for biosensors. We investigate using these techniques to print electrically conductive fine line structures for electroluminescent (E/L) light sources. Approach:The viability of using microcontact printing as a process for electronics fabrication is investigated. Polydimethylsiloxane (PDMS) stamps inked with alkanethiol compounds form Self Assembled Monolayers (SAM) on substrate surfaces, acting as the resist to subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Roll‐to‐roll methods are effective at processing large areas and high volumes and as such are an important area of current research; some examples are gravure, contact, stamp transfer, doctor blading, and flexographic printing [5–10]. Soft lithography processing has also been investigated [11, 12] and patterned polymeric anodes have successfully been created using a peel‐off soft lithography method [13]. Other developments in processing techniques include depositing different layer materials using different methods (a combination of both solution based and thermal deposition) [9, 10, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Roll‐to‐roll methods are effective at processing large areas and high volumes and as such are an important area of current research; some examples are gravure, contact, stamp transfer, doctor blading, and flexographic printing [5–10]. Soft lithography processing has also been investigated [11, 12] and patterned polymeric anodes have successfully been created using a peel‐off soft lithography method [13]. Other developments in processing techniques include depositing different layer materials using different methods (a combination of both solution based and thermal deposition) [9, 10, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, interesting properties carried by soft materials enable them to be better suited for various applications like microfluidics devices, large area deposition, or unusual material/shape patterning. Soft materials can replicate features with nanometric size at low cost; they are widely compatible with other materials and with self-assembling process. Hence, this leads to high application potential such as model systems to study interfacial phenomena relevant to etching protection, biological and chemical sensors, or molecular electronics. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Hence, this leads to high application potential such as model systems to study interfacial phenomena relevant to etching protection, [6][7][8] biological and chemical sensors, 9 or molecular electronics. 1,10,11 As a consequence, dynamical properties involved in microcontact printing processes have attracted much interest and deserve to be fully understood. The use of solid ink enables the formation of patterns with lateral resolutions down to 50 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The present study has shown that the flexographic printing process can be used to produce high surface area porous electrodes for use in viable supercapacitors and these might be used to power printed displays [6,7]; however, several challenges still remain. The first challenge is to achieve complete coverage of the silver layer, and the second is to improve the capacitance.…”
Section: Future Workmentioning
confidence: 99%